Phosphodiesterase as a New Therapeutic Target for the Treatment of Spinal Cord Injury and Neurodegenerative Diseases - Paterniti, Irene; Esposito, Emanuela; Cuzzocrea, Salvatore (Current Medicinal Chemistry, 2014)
Interest in Central Nervous System (CNS) inflammation has rapidly grown over the past decade driven by the increasing evidence indicating that chronic inflammation and neuroinflammation in the brain may play an important role in the progressive neuronal cell death in many chronic CNS diseases, such as Alzheimer and Parkinson’s diseases, traumatic brain injury, spinal cord injury (SCI), as well as pathologies associated with CNS infections. In peripheral tissues, generally inflammation has a protective role limiting the survival and proliferation of invading pathogens, promoting tissue repair and recovery. This innate response normally resolves over a few weeks, accompanyied by tissue repair aided by macrophages recruited to the site. However, when the inflammatory response does not undergo resolution, it might turn into chronic inflammation. Any chronic inflammatory process can damage healthy tissue and the brain may be particularly vulnerable, since destroyed neurons can not be replaced. Recently, several reports have suggested that phosphodiesterases (PDEs) are new targets for central nervous system (CNS) diseases. All the PDEs are expressed in the CNS, making this gene family a particularly attractive source of new targets for the treatment of psychiatric and neurodegenerative disorders. Significantly, all neurons express multiple PDEs, which differ in cyclic nucleotide specificity, affinity, regulatory control and subcellular compartmentalization. Therefore, PDEs inhibition represents a mechanism through which it could be possible to precisely modulate neuronal activity. In this article, we review the current state of art of PDEs in the CNS diseases associated with neuroinflammation.
Keywords: Alzheimer’s disease